2023
DOI: 10.1021/acs.langmuir.3c00063
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Impact Dynamics on Biomimetic Replica of Yellow Rose Petals: Rebound to Micropinning Transition

Abstract: Rose petals exhibit a phenomenal wetting property of being sticky and superhydrophobic simultaneously. A recent study has shown that for short timescales, associated with drop impact phenomenon, lotus leaf and rose petal replicas exhibit similar wettability, thereby highlighting the difference between long and short time wettability. Also, short time wetting on rose petals of different colors remains completely unaddressed, as almost all existing study on wetting of rose petals have been performed with the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Such a surface may behave like an “adhesive Cassie”-type surface. 68,69 The water contact angle on the irradiated surface was calculated theoretically using the Cassie model by considering the average pore diameter of 50 nm (Fig. 1(c)) and a thickness of 1.01 μm for the nano-network, yielding a contact angle of about 92°, which is within the range of observed angles in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Such a surface may behave like an “adhesive Cassie”-type surface. 68,69 The water contact angle on the irradiated surface was calculated theoretically using the Cassie model by considering the average pore diameter of 50 nm (Fig. 1(c)) and a thickness of 1.01 μm for the nano-network, yielding a contact angle of about 92°, which is within the range of observed angles in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Many studies have reported on fabricating artificial microtextured surfaces mimicking nature. The outcomes of droplet impact on these surfaces are also reported, such as recent studies mimicking taro leaf and yellow rose petals . The dynamic behavior of the impacting droplet depends on the droplet’s initial We and the microtexture shape and size of the surface.…”
Section: Interaction Of Liquid With Surfacesmentioning
confidence: 93%
“…Bouncing of droplets gives rise to an amazing diversity of physical events. A broad range of physical phenomena is associated with the flow in the drop, initiated by its impact onto a solid substrate. The scenarios of drop impact depend on the impact velocity, its direction relative to the surface, the drop radius, the physical properties of the liquid (its density, surface tension, viscosity, and viscoelasticity), the topography of the surface and its wettability, ,, isothermal effects, and air entrapment . Droplet impact plays a key role in a variety of technological situations, including the building industry, development of anti-icing surfaces, painting/coating, spray technology, corrosion of turbine blades and aircraft, oil separation, heat transfer, and electricity generation. , Naturally occurring impact of rain droplets with leaves and soil is also of great interest. , Rapid progress in understanding the complicated interplay of processes occurring during droplet impact came with the development of rapid imaging experimental techniques …”
Section: Introductionmentioning
confidence: 99%